Improving the Quality of the Indoor Environment Utilizing Desiccant-Assisted Heating, Ventilating, and Air Conditioning Systems - Straus, David; Larranaga, M.D.; Karunasena, Enusha; Holder, H.W.; Beruvides, M.G. (IntechOpen, 2011)
None